Analisis Kendala Mahasiswa Program Studi Pendidikan Matematika Semester 2 dalam Menulis Karya Ilmiah - Wulandari, Inayah; Maisyaroh, Irma; Mufidah, Nur (Jurnal Likhitaprajna, 2023)
This study aims to determine the obstacles experienced by early semester students in writing scientific papers and solutions in dealing with these obstacles. This research was conducted in April 2023, at the Nahdlatul Ulama 'Pasuruan Institute of Technology and Science. The method used is descriptive skinative method with phenomenological approach. Data collection was carried out by observation, interviews, and using research instruments in the form of questionnaires. The results showed several obstacles experienced by students in writing both in the form of internal and external obstacles as well as solutions to these obstacles.